THE IMPACT OF GAME-BASED LANGUAGE LEARNING ON THE MOTIVATION AND SPEAKING FLUENCY IN MANDARIN CHINESE OF INDONESIAN UNIVERSITY STUDENTS - Mufadhol Mufadhol; Li Wi; Zhang Li (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Mandarin Chinese has become increasingly important in higher education in Indonesia, yet many university students experience low motivation and limited speaking fluency due to linguistic complexity and anxiety in oral communication. This study aims to examine the impact of Game-Based Language Learning on students’ learning motivation and speaking fluency in Mandarin Chinese. The research employed a quasi-experimental design with a non-equivalent control group, involving sixty Indonesian university students enrolled in Mandarin courses. Data were collected through motivation questionnaires, standardized speaking fluency tests, and classroom observations, and were analyzed using descriptive statistics, inferential tests, and qualitative thematic analysis. The findings reveal that students who participated in game-based learning activities demonstrated significantly higher motivation levels and greater improvements in speaking fluency compared to those receiving conventional instruction. Game-based activities reduced speaking anxiety, increased participation, and provided meaningful opportunities for spontaneous oral practice. The study concludes that Game-Based Language Learning is an effective pedagogical approach for enhancing both affective and communicative aspects of Mandarin speaking instruction. Integrating structured game-based activities into university Mandarin programs can support learner engagement, improve oral fluency, and address persistent challenges in foreign language learning contexts. These findings offer practical implications for curriculum design and innovative language pedagogy development.